Fluoroscopy-free RIRS on the second session after ureteral stent placement. Issue 1 (February 2023) - Bozkurt, Muammer; Seker, Kamil Gokhan
Aim: Fluoroscopy is used in some stages of the conventional Retrograde Intrarenal Surgery (RIRS) procedure and is beneficial. On the other hand, radiation exposure is its most obvious disadvantage. As a subgroup, we aimed to show that fluoroscopy-free technique is safe and effective in patients who underwent RIRS after passive dilatation. Materials and methods: Between October 2018 and April 2020, 54 cases of second session RIRS of renal stones performed by a single surgeon were retrospectively evaluated. Patients' demographic characteristics (age, gender), stone features (laterality, size, number, volume, and location), mean operative time, and, perioperative and postoperative complications, as well as the stone-free rate (SFR), were all retrospectively evaluated. The results were classified as stone free, clinical insignificant residual fragments (CIRF), and presence of residual stones. Complications were graded using the Clavien–Dindo classification system. We used a modified surgical technique. Results: All of complications were minor. There were no major complications (Clavien grade III–IV). The stone-free rate was 70.3% (38/54) on the first day after surgery and 83.3% (45/54) 1 month afterward, respectively. If we accept the absence of residual stone as success, we can say that it is about 91% successful in the first month. Conclusion: This technique has a high stone-free success rate and a low complication rate without the use of radiation. For surgeons experienced in endourology, we can say that the fluoroscopy-free technique is safe and effective in secondary-session RIRS cases which passive dilatation was performed by inserting a ureteral catheter before.